Seeds of Life : Women and Agricultural Biodiversity in Africa - Easton, Peter (World Bank, Washington, DC, 2012)
One of the down-sides of worldwide agricultural development, has been the replacement of native plant species by marketable crops, accompanied by a reduction in the diversity of the seed stock. This accounts for the disappearance of plants with potential medicinal uses, particularly in high biodiversity areas, and, the crowding out of native diversity of edible species by standard, sometimes genetically altered by commercial farming demands, is an equally serious problem. Indigenous knowledge of edible plants is one key "pool" of biodiversity in Africa - one in which women play a vital role. The note looks at bean farming in Kenya, where evidence shows that in pre-colonial times a large variety of bean species was cultivated, which constituted a critical element of rural people's diet, and a rich source of protein. Traditionally, women grew, and conserved multiple seed stocks, as a hedge against disease, and unpredictable climate changes. However, the colonial agricultural extension service eliminated multi-cropping - a phenomenon that brought negative consequences for nutrition, biodiversity, and soil fertility. This case unfortunately was not an isolated one, though fortunately efforts to coordinate a participatory research program on gender roles in agriculture, and plant breeding are underway, headed by the International Center for Tropical Agriculture (CIAT).